Morphology of the ferritin iron core by aberration corrected scanning transmission electron microscopy - Richard Palmer (Nanotechnology, 2016)
As the major iron storage protein, ferritin stores and releases iron for maintaining the balance of iron in fauna, flora, and bacteria. We present an investigation of the morphology and iron loading of ferritin (from equine spleen) using aberration-corrected high angle annular dark field scanning transmission electron microscopy. Atom counting method, with size selected Au clusters as mass standards, was employed to determine the number of iron atoms in the nanoparticle core of each ferritin protein. Quantitative analysis shows that the nuclearity of iron atoms in the mineral core varies from a few hundred iron atoms to around 5000 atoms. Moreover, a relationship between the iron loading and iron core morphology is established, in which mineral core nucleates from a single nanoparticle, then grows along the protein shell before finally forming either a solid or hollow core structure.